Credit market choice - Nina Boyarchenko; Anna M. Costello; Or Shachar (Federal Reserve Bank of New York, 2018)
Which markets do institutions use to change exposure to credit risk? Using a unique data set of transactions in corporate bonds and credit default swaps (CDS) by large financial institutions, we show that simultaneous transactions in both markets are rare, with an average institution having an 11 percent probability of transacting in both the CDS and bond markets in the same entity in an average week. When institutions do transact in both markets simultaneously, they increase their speculative positions in CDS by 13 cents per dollar of bond transactions, and their hedging positions by 13 cents per dollar of bond transactions. We find evidence that, during the post-crisis rule implementation period, the incentive to use paired transactions is reduced but so is the incentive to take naked positions in the CDS market. When single name contracts become eligible for central clearing, globally systemically important institutions become more likely to use single name CDS contracts. Finally, we show that, in the aggregate, U.S. globally systemically important institutions reduce their exposure to corporate credit risk in the rule implementation period, primarily through reducing the amount of credit protection sold in the index CDS market.
Keywords: G11; G18; G20; G28; 330; CDS; corporate bonds; hedging; regulation; CCPs